Why Performance Information Use Requires a Managerial Identity: Evidence from the Field of Human Services. Issue 2 (4th March 2019) - Pfiffner, Roger
Abstract: Previous research suggests that civil servants can perceive their role differently and that these differing perceptions also influence their responses to managerial reform programs. Yet there is little research examining how different role perceptions influence the application of performance measurement. Using survey data from 742 human service organizations in Switzerland, the present study addresses this gap by investigating how professional and managerial role identities affect managers' use of performance information. The results support the hypotheses that role identities indirectly influence the application of performance information through the effects on role conflict that may occur when managerial professionals measure the performance of their organizations. A lack of resources, stringent political control, and poor information quality are also found to be associated with role conflict and a limited use of performance information.